PENERAPAN METODE BERPIKIR ILMIAH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA - Faroby, Firman Al; Hanifah, Nurdinah; Julia, Julia (Jurnal Pena Ilmiah, 2019)
AbstractDuring the learning process of Social Sciences on Types of Business and Economic Activities material, teachers still uses conventional learning which is Teacher Centered Learning (TCL). This study was conducted on class VB students at Cikoneng Elementary School in Ganeas Sub-District, Sumedang District by implementing a Classroom Action Research (CAR). This Classroom Action Research was conducted in three cycles. As for the data obtained on are as follows, the student critical thinking ability test at first cycle reached 32%, at second cycle increased 68%, and at third cycle increased and reached the target of 84%. Then the student learning outcomes test at first cycle reached 64%, at second cycle increased 76%, and at third cycle increased and reached the target of 92%. Thus this study successfully improves students’ critical thinking ability and learning outcomes on VB class at Cikoneng Elementary School in Ganeas Sub-District, Sumedang District.